2022
DOI: 10.1109/tia.2022.3160135
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Predictive Compensation of Flicker, Voltage Dips, Harmonics and Interharmonics in Electric Arc Furnaces

Abstract: In this research work, deep machine learning based methods together with a novel data augmentation are developed for predicting flicker, voltage dip, harmonics and interharmonics originating from highly time-varying electric arc furnace (EAF) currents and voltage. The aim with the prediction is to counteract both the response and reaction time delays of active power filters (APFs) specifically designed for electric arc furnaces (EAF). Multiple synchronous Reference frame (MSRF) analysis is used to decompose th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Deep machine learning-based algorithms and novel data augmentation are used to forecast flicker, voltage dip, harmonics, and interharmonics from highly time-varying electric arc furnace (EAF) currents and voltage in [28]. The prediction aims to reduce response and reaction time delays in electric arc furnaces (EAF)-specific active power filters (APFs).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Deep machine learning-based algorithms and novel data augmentation are used to forecast flicker, voltage dip, harmonics, and interharmonics from highly time-varying electric arc furnace (EAF) currents and voltage in [28]. The prediction aims to reduce response and reaction time delays in electric arc furnaces (EAF)-specific active power filters (APFs).…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, many papers in specialized journals present research on the presence of harmonic currents, load unbalances, or overcurrents. In recent years, there has been a significant amount of research conducted on power quality and harmonic currents, focusing on the utilization of artificial intelligence and machine learning techniques [22][23][24][25][26][27][28][29][30]. Our research also focuses on utilizing deep learning and recurrent neural networks (RNN) for predicting the power factor in hot rolling mils factories.…”
Section: Introductionmentioning
confidence: 99%
“…Hasan et al [20] showed that SG filter can remove harmonics and does not cause distortion of grid voltage signal. In addition to the SG filter, commonly used signal smoothing methods include Wl denoising [21], Bw filter [22], Chebyshev filter [23], and Et filter [24]. It can be seen that these methods have been widely used in the smoothing of different kinds of signals.…”
Section: Nomenclaturementioning
confidence: 99%